Soil Bacterial and Fungal Richness Forecast Patterns of Early Pine Litter Decomposition - Albright, Michaeline B. N.; Johansen, Renee; Thompson, Jaron; Lopez, Deanna; Gallegos-Graves, La V.; Kroeger, Marie E.; Runde, Andreas; Mueller, Rebecca C.; Washburne, Alex; Munsky, Brian; Yoshida, Thomas; Dunbar, John (Frontiers in Microbiology, 2020)
Discovering widespread microbial processes that drive unexpected variation in carbon cycling may improve modeling and management of soil carbon [2-4]. A first step is to identify community features linked to carbon cycle variation. We addressed this challenge using an epidemiological approach with 206 soil communities decomposing Ponderosa pine litter in 618 microcosms. Carbon flow from litter decomposition was measured over a six-week incubation. Cumulative CO2 from microbial respiration varied 2-fold among microcosms and dissolved organic carbon (DOC) from litter decomposition varied 5-fold, demonstrating large functional variation despite constant environmental conditions where strong selection is expected. To investigate microbial features driving DOC concentration, two microbial community cohorts were delineated as “high” and “low” DOC. For each cohort, communities from the original soils and from the final microcosm communities after the six-week incubation with litter were taxonomically profiled. A logistic model including total biomass, fungal richness, and bacterial richness measured in the original soils or in the final microcosm communities predicted the DOC cohort with 72 (P<0.05) and 80 (P<0.001) percent accuracy, respectively. The strongest predictors of the DOC cohort were biomass and either fungal richness (in the original soils) or bacterial richness (in the final microcosm communities). Successful forecasting of functional patterns after lengthy community succession in a new environment reveals strong historical contingencies. Forecasting future community function is a key advance beyond correlation of functional variance with end-state community features. The importance of taxon richness—the same feature linked to carbon fate in gut microbiome studies—underscores the need for increased understanding of biotic mechanisms that can shape richness in microbial communities independent of physicochemical conditions.